Cardiovascular, liver, and renal toxicity associated with an intravenous ferric carboxymaltose similar versus the originator compound - Toblli JE; Cao G; Rico L; Angerosa M (Dove Medical Press, 2017)
Jorge E Toblli, Gabriel Cao, Luis Rico, Margarita Angerosa Laboratory of Experimental Medicine, Hospital Alemán, School of Medicine, University of Buenos Aires, Buenos Aires, Argentina Background: Ferric carboxymaltose (FCM) is a stable, non-dextran-based intravenous iron complex used to treat iron deficiency of various etiologies. As FCM is a nonbiological complex drug and cannot be fully characterized by physicochemical analyses, it is important to demonstrate in nonclinical models that FCM similars (FCMS) have similar biodistribution. Materials and methods: A total of 30 nonanemic rats were treated weekly with 40 mg iron/kg body weight intravenous FCM, FCMS, or isotonic saline (controls) for 4 weeks. Blood pressure, liver enzymes, and renal function were evaluated. In liver, heart, and kidney tissue, markers for oxidative stress (malondialdehyde to assess lipid peroxidation and antioxidant enzymes) and inflammation (TNFα and IL6) were measured. Iron deposits were localized. Results: The FCMS-treated group had significantly lower blood pressure, higher liver enzymes, increased proteinuria, and reduced creatinine clearance versus the FCM and control groups by day 29. Serum iron and transferrin saturation were significantly higher with FCMS versus FCM or controls. Iron deposition was altered in FCMS-treated animals, with decreased ferritin deposits and iron deposition outside the physiological storage compartments. Markers for lipid peroxidation and antioxidant-enzyme activity were significantly increased after FCMS administration versus FCM and controls, as were inflammatory markers. Conclusion: Results from this blinded nonclinical study demonstrated significant differences between the originator FCM and this FCMS. Keywords: ferric carboxymaltose, Ferinject, Orofer, follow-ons, nonbiological complex drugs, oxidative stress